Characterization of spaces of type W and pseudo-differential operators of infinite order involving fractional Fourier transform - Upadhyay S.K.; Kumar A.; Dubey J.K. (My University, 2025)
The characterization of W-type spaces is investigated and various properties of pseudo-differential operators are studied by using the fractional Fourier transform. © 2014 Springer Basel.